2020
DOI: 10.1136/archdischild-2019-318001
|View full text |Cite
|
Sign up to set email alerts
|

Infection is associated with one in five childhood deaths in England and Wales: analysis of national death registrations data, 2013–15

Abstract: ObjectiveTo estimate the contribution of infections to childhood deaths in England and Wales over a 3-year period.DesignRetrospective analysis of national electronic death registration data.SettingEngland and Wales.PatientsChildren aged 28 days to 15 years who died during 2013–15.Main outcome measuresThe proportion of children who died of infection compared with total deaths over 3 years; the main pathogens responsible for infection-related deaths in different age groups; comparison with similar data from 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Consequently, children with a positive SARS-CoV-2 test who die of other causes and those who succumb to their underlying conditions will be included in those figures. More recently, death registrations with mention of SARS-CoV-2/COVID-19 are routinely reported by the UK Office for National Statistics (ONS)[ 18 ] but, as we and others have previously reported, these too are limited by the information available on the death certificate, making it difficult to assess the contribution of SARS-CoV-2 infection to death [ 19 , 20 ]. During the first 12 months of the pandemic, for example, only 40% of deaths in CYP with confirmed infection in England were due to COVID-19 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, children with a positive SARS-CoV-2 test who die of other causes and those who succumb to their underlying conditions will be included in those figures. More recently, death registrations with mention of SARS-CoV-2/COVID-19 are routinely reported by the UK Office for National Statistics (ONS)[ 18 ] but, as we and others have previously reported, these too are limited by the information available on the death certificate, making it difficult to assess the contribution of SARS-CoV-2 infection to death [ 19 , 20 ]. During the first 12 months of the pandemic, for example, only 40% of deaths in CYP with confirmed infection in England were due to COVID-19 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most children had meningitis or sepsis reflecting the success of our recruitment through our charity partner Meningitis Now. Health professionals (female n = 9, male 5) worked in General Practice [ 5 ], Emergency Care [ 5 ], Ambulance Service [ 2 ] and ‘Other’ health services [ 4 ]. Age range; between 21–29 and 50–59 years.…”
Section: Resultsmentioning
confidence: 99%
“…Globally, infection remains the leading cause of child mortality [ 1 ]. The most recent analysis of child mortality data (from 2013–15) in England and Wales found that infection was associated with 20% of all childhood deaths [ 2 ]. Child Death Reviews (CDR), which aim to identify modifiable factors in any child’s death, are reported by Local Safeguarding Children’s Boards and have been collated into annual reports for England by NHS Digital since 2018 and previously by the Department for Education [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…When research does include children with comorbidities, it usually focuses on specific types of comorbidities, such as febrile neutropenia [ 14 ]. The most compelling evidence that shows how children with comorbidities form a very fragile population comes from a recent key paper, showing half of the infection-related deaths in the UK occur in children with comorbidities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%